Martian low‐altitude magnetic topology deduced from MAVEN/SWEA observations. Issue 2 (17th February 2017) - Xu, Shaosui; Mitchell, David; Liemohn, Michael; Fang, Xiaohua; Ma, Yingjuan; Luhmann, Janet; Brain, David; Steckiewicz, Morgane; Mazelle, Christian; Connerney, Jack; Jakosky, Bruce
Abstract: The Mars Atmosphere and Volatile Evolution mission has obtained comprehensive particle and magnetic field measurements. The Solar Wind Electron Analyzer provides electron energy‐pitch angle distributions along the spacecraft trajectory that can be used to infer magnetic topology. This study presents pitch angle‐resolved electron energy shape parameters that can distinguish photoelectrons from solar wind electrons, which we use to deduce the Martian magnetic topology and connectivity to the dayside ionosphere. Magnetic topology in the Mars environment is mapped in three dimensions for the first time. At low altitudes (<400 km) in sunlight, the northern hemisphere is found to be dominated by closed field lines (both ends intersecting the collisional atmosphere), with more day‐night connections through cross‐terminator closed field lines than in the south. Although draped field lines with 100 km amplitude vertical fluctuations that intersect the electron exobase ( 160–220 km) in two locations could appear to be closed at the spacecraft, a more likely explanation is provided by crustal magnetic fields, which naturally have the required geometry. Around 30% of the time, we observe open field lines from 200 to 400 km, which implies three distinct topological layers over the northern hemisphere: closed field lines below 200 km, open field lines with foot points at lower latitudes that pass over the northern hemisphere from 200 to 400 km, and draped interplanetary magnetic field above 400 km. This study also identifies open field lines with one end attached to the dayside ionosphere and the other end connected with the solar wind, providing a path for ion outflow. Key Points: Pitch angle‐resolved electron energy shape parameters are used to deduce magnetic topology Closed magnetic field lines dominate low altitudes (<400 km) of the northern hemisphere on the dayside The 3‐D view of the Martian magnetic topology is presented for the first time